G311(P) Auditof spinal ultrasound (su) for neonatal sacral dimples. (27th April 2015) - Pandya, D; Kayode, O; Gandhi, A
Abstract : Background: Isolated sacral dimples are common and it is increasingly recognised that most are not linked to spinal dysraphism. Based on their features they can be classified into low risk and high risk. The Royal college of Radiologists guidance states that the high risk dimples (large, base not visible, >25 mm from anus or >5mm from midline or associated with additional stigmata of spinal dysraphism) should be investigated with SU. Objective: To determine whether hospital guidelines specific to sacral dimples are being followed and to ascertain the yield of SU. Method: A cohort of neonates from the entire Trust who received a spinal ultrasound scan due to the presence of a sacral dimple between 2007–2011 were included. Information was gathered from clinical letters, referral forms, and the presence or absence of a spinal abnormality was assessed by evaluating the ultrasound scan reports. Results: 94 neonates underwent SU for sacral dimple. 89 (95%) infants with sacral dimple underwent SU, 4 (4%) SUS with additional MRI scanning and 1 (1%) SUS with plain radiography. 63 (66%) of sacral dimples were described in the referral as high risk, 7(7%) as low risk and 24 (25%) sacral dimples had too little detail/description in their referrals to determine the risk. Therefore, over the 3 year duration, only 7% of sacral dimples were low risk in nature so were ultra-sounded against hospital guidelines. 'Indeterminate dimples' had limited description on the radiology request form, assuming these were also low risk in nature, 31 (33%) sacral dimples were ultra-sounded against guidelines. 13% of high risk sacral dimples in this audit revealed a spinal abnormality upon imaging. No abnormality was detected in cases not classed as high risk. This is in line with other reports and supports the current practice of selective SU in newborns with high risk dimples. Conclusion: Trust guidelines are being followed, to some degree. 25% of ultra-sounded sacral dimples were not adequately described on referral. A significant number of SU are still done for low risk dimples and these can be safely avoided reducing cost and parental anxiety.